PENGARUH MODEL PEMBELAJARAN PROJECT BASED LEARNING BERBANTUAN MEDIA WORDWALL TERHADAP KEMAMPUAN MENULIS TEKS DRAMA SISWA KELAS XI SMA NEGERI 10 MEDAN - Margaret Kaloko, Debi; Simanjuntak, Harlen; Br. Saragih, Renita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine students' drama writing skills before and after using the Project Based Learning (PjBL) model with the aid of Wordwall media, and to determine the model's effect on the drama writing skills of eleventh-grade students at SMA Negeri 10 Medan. This study used an experimental method with a one-group pretest-posttest design. The population in this study were all eleventh-grade students of SMA Negeri 10 Medan, while the research sample consisted of 35 students. The research instrument used was a drama writing test given in the form of a pretest and posttest. The research data were analyzed using statistical analysis techniques to determine improvements in students' writing skills and hypothesis testing using a t-test. The results showed that students' drama writing skills before using the Project Based Learning model with the aid of Wordwall media were still relatively low with an average score of 55.57. After being given treatment using the Project Based Learning model with the aid of Wordwall media, students' drama writing skills increased with an average score of 77.42. This improvement indicates that students are beginning to be able to construct a clearer storyline, develop character traits, write dialogue appropriate to the story context, and use more effective language. Based on the results of the hypothesis testing using the t-test, the calculated t-value was greater than the table t-value at a significance level of α = 0.05, thus H₀ was rejected and Hₐ was accepted